Correction: Identification of active sites for CO2 hydrogenation in Fe catalysts by first-principles microkinetic modelling. Issue 35 (26th August 2020) - Han, Seung Ju; Hwang, Sun-Mi; Park, Hae-Gu; Zhang, Chundong; Jun, Ki-Won; Kim, Seok Ki
Abstract : Correction for 'Identification of active sites for CO2 hydrogenation in Fe catalysts by first-principles microkinetic modelling' by Seung Ju Han et al., J. Mater. Chem. A, 2020, 8, 13014–13023, DOI: ; 10.1039/D0TA01634A .